2017
DOI: 10.1021/acsomega.7b01457
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Detection of Capsaicin in Oil for Fast Identification of Illegal Cooking Oil by SERRS

Abstract: Discrimination of illegal cooking oil is a conundrum in the fields of analytical chemistry and food safety due to complicated sample systems, lack of common targets, and stringent demand of ultrahigh detection sensitivity for corresponding analytical methods. Capsaicin, one of the exogenous molecules that is subsistent in recycled kitchen waste oils, can be regarded as a target for illegal cooking oil identification. Nowadays, tracing capsaicin in oils is implemented mainly by high-performance liquid chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Surface-enhanced Raman spectroscopy (SERS) is a simple and nondestructive technique which promises numerous applications such as the trace detection of drugs, explosives, food contaminants, biological entities, and environmental hazardous gases. In SERS technique, the intensity of inelastically scattered photon from the molecule can be enhanced using the long-range electromagnetic (EM) field and short-range chemical effects. EM enhancement is attributed to the localized surface plasmon resonance (LSPR) in the near-field metallic surface, and the chemical enhancement is because of the charge transfer (CT) mechanism between the substrate and the analyte.…”
Section: Introductionmentioning
confidence: 99%
“…Surface-enhanced Raman spectroscopy (SERS) is a simple and nondestructive technique which promises numerous applications such as the trace detection of drugs, explosives, food contaminants, biological entities, and environmental hazardous gases. In SERS technique, the intensity of inelastically scattered photon from the molecule can be enhanced using the long-range electromagnetic (EM) field and short-range chemical effects. EM enhancement is attributed to the localized surface plasmon resonance (LSPR) in the near-field metallic surface, and the chemical enhancement is because of the charge transfer (CT) mechanism between the substrate and the analyte.…”
Section: Introductionmentioning
confidence: 99%
“…Secondhand cooking oil has been a major issue in China, with annual consumption of over 3 million tons. 5 In this study, we demonstrated that MagLev could be potentially used for the detection of secondhand cooking oil. As shown in Fig.…”
Section: Maglev-based Detection Of Secondhand Cooking Oilmentioning
confidence: 73%
“…For example, up to 3 million tons of secondhand cooking oils have owed back to Chinese dining tables annually. 5 These dirty secondhand cooking oils, also called "underground drainage oil" in China, generally refer to all kinds of inferior cooking oils, such as the waste oil that has been processed and reclaimed from leovers. These types of oils are extremely harmful to human health if consumed frequently.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, capsaicin is unavoidable and remains in the used oil after the frying process of pepper. Typically, it is difficult to completely remove capsaicin from recycled cooking oil with the current technology (Liu et al, 2017). Thus, capsaicin is regarded as the characteristic marker for the identification of recycled cooking oil (Lu et al, 2020;Zhou et al, 2018).…”
Section: Introductionsmentioning
confidence: 99%